AN ANALYSIS OF METAPHORS IN MADISON BEER’S SELECTED SONG LYRICS - Sotyarini, Ririn (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2023)
Metaphors were frequently found in songs and raised curiosity among the listeners to find out the true meaning. The songs released by Madison Beer are interesting to be discussed. Madison Beer is a young American singer, model, and songwriter who is known worldwide. She released her debut single “Melodies” in 2013. In 2018 Beer released her debut EP, “As She Pleases”. Her songs are full of romantic, yet sad stories relate to real life of female teenagers. The writer applied library research and qualitative descriptive research which intentionally reveals the types of metaphors in her two selected songs; “Follow The White Rabbit” from her Album Life Support, and “Reckless”, a single from Silence Between Songs. The objective of this research is conducted by applying George Lakoff and Johnson’s theory about types of metaphors such as structural metaphor, a metaphor which put one concept into another concept, orientation metaphor which deals with a spatial orientation that is derived from physical and cultural experiences, and ontological metaphor related to the experience of physical objects and substances. The first song “Follow The White Rabbit” tells about a story of a relationship. This song was strongly influenced by the movies The Matrix (Film) and Alice in Wonderland (Film). “Reckless” tells a sad story about betrayal in relationship which is sweetly performed by Beer. Furthermore, the writer found 16 data of metaphors, 9 structural metaphor, 5 ontological metaphor, and 2 orientation metaphor.